Heart Failure Risk Associated With Rheumatoid Arthritis–Related Chronic Inflammation. Issue 10 (18th May 2020) - Ahlers, Michael J.; Lowery, Brandon D.; Farber‐Eger, Eric; Wang, Thomas J.; Bradham, William; Ormseth, Michelle J.; Chung, Cecilia P.; Stein, C. Michael; Gupta, Deepak K.
Abstract : Background: Inflammation may contribute to incident heart failure (HF). Rheumatoid arthritis (RA), a prototypic inflammatory condition, may serve as a model for understanding inflammation‐related HF risk. Methods and Results: Using the Vanderbilt University Medical Center electronic health record, we retrospectively identified 9889 patients with RA and 9889 control patients without autoimmune disease matched for age, sex, and race. Prevalent HF at entry into the electronic health record or preceding RA diagnosis was excluded. Incident HF was ascertained using International Classification of Diseases, Ninth Revision (ICD‐9), codes and medications. Over 177 566 person‐years of follow‐up, patients with RA were at 21% greater risk of HF (95% CI, 3–42%) independent of traditional cardiovascular risk factors. Among patients with RA, higher CRP (C‐reactive protein) was associated with greater HF risk ( P <0.001), while the anti‐inflammatory drug methotrexate was associated with ≈25% lower HF risk ( P =0.021). In a second cohort (n=115) of prospectively enrolled patients with and without RA, we performed proteomics and cardiac magnetic resonance imaging to discover circulating markers of inflammation associated with cardiac structure and function. Artemin levels were higher in patients with RA compared with controls ( P =0.009), and higher artemin levels were associated with worse ventricular end‐systolic elastance and ventricular‐vascular coupling ratio ( P =0.044 and P =0.031, respectively). Conclusions: RA, a prototypic chronic inflammatory condition, is associated with increased risk of HF. Among patients with RA, higher levels of CRP were associated with greater HF risk, while methotrexate was associated with lower risk.